The new scope of knowledge spillover to develop the functionality of technologies. (1st October 2010) - Shibata, Yosuke; Saiki, Tomoko
The purpose of this study is to propose a new scope of knowledge spillover between technologies by demonstrating how knowledge spillover affects the development of technologies. We use the number of patent applications as proxy of development of technologies. As a case of this study, we group energy technologies, lithium-ion battery (LIB) as a product, into two groups using international patent classification (IPC). We group them into 'simple technology' which belongs to one technology segment of LIB, and 'complex technology' which belongs to two or more technology segments. The result shows that, in the innovation process of LIB, R&D fields have diversified gradually according to the increase of complex technology. It is also shown that simple technology as technology groups leading the innovation is replaced by complex technology, which is suggested to involve knowledge spillover, in the electrode technology.